Inspiratory muscle training in intensive care unit patients: A Systematic review - Nurul Imam; Taufan Citra Darmawan; Khalifatus Zuhriyah Alfianti; Welmince Paulina Nggorong; Ananda Patuh Padaallah (KHD-Production, 2025)
Critical patients with ICU room treatment have high morbidity and mortality. Prolonged use of mechanical ventilation can result in a reduction in the strength of the respiratory muscles. The purpose of this review article is to explain the effectiveness of the implementation of IMT in Intensive Care Unit patients. The research design used the PRISMA guideline with a literature search strategy on the Scopus database (n=10), ProQuest (n=1), Web of Science (n=913), PubMed (n=291), and Google Scholar (n=800), with the keyword